2015
DOI: 10.1111/jonm.12328
|View full text |Cite
|
Sign up to set email alerts
|

Inactive nurses in Taiwan: human capital, intention to return to hospital nursing, and incentives for returning

Abstract: The findings confirm the human capital of inactive nurses and provide concrete directions for nursing managers to follow when recruiting inactive nurses to hospital nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Moreover, Yu et al . () reported that for 77.4% of INs, working only day shifts was an incentive for returning to active nursing. This puts INs and NAs in conflict, as they have different concerns regarding return to clinical work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, Yu et al . () reported that for 77.4% of INs, working only day shifts was an incentive for returning to active nursing. This puts INs and NAs in conflict, as they have different concerns regarding return to clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that INs experience difficulties when re-entering the workforce, including difficulties with balancing work and family life, particularly with night-shift requirements (Roberts et al 2005, Tanaka et al 2008. Moreover, Yu et al (2015) reported that for 77.4% of INs, working only day shifts was an incentive for returning to active nursing. This puts INs and NAs in conflict, as they have different concerns regarding return to clinical work.…”
Section: Nurse Administrators' Considerations For Recruiting Inactivementioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most persistent work‐related challenges in the health care industries are the high levels of stress, burnout and turnover associated with the work (Boamah & Laschinger , Yu et al . ). Work–life balance practices are intended to provide employees with job flexibility in order to accommodate family and other life responsibilities.…”
Section: Introductionmentioning
confidence: 97%